Dysregulation of ACE (Angiotensin-Converting Enzyme)-2 and Renin-Angiotensin Peptides in SARS-CoV-2 Mediated Mortality and End-Organ Injuries. Issue 2 (30th November 2021) - Wang, Kaiming; Gheblawi, Mahmoud; Nikhanj, Anish; Munan, Matt; MacIntyre, Erika; O'Neil, Conar; Poglitsch, Marko; Colombo, Daniele; Del Nonno, Franca; Kassiri, Zamaneh; Sligl, Wendy; Oudit, Gavin Y.
Abstract : Supplemental Digital Content is available in the text. Abstract : ACE (angiotensin-converting enzyme)-2 as the target for SARS-CoV-2 also negatively regulates the renin-angiotensin system. Pathological activation of ADAM17 (A disintegrin and metalloproteinase-17) may potentiate inflammation and diminish ACE2-mediated tissue protection through proteolytic shedding, contributing to SARS-CoV-2 pathogenesis. We aim to examine plasma soluble ACE2 and angiotensin profiles in relation to outcomes by enrolling consecutive patients admitted for COVID-19 with baseline blood collection at admission and repeated sampling at 7 days. The primary outcome was 90-day mortality, and secondary outcomes were the incidence of end-organ injuries. Overall, 242 patients were included, the median age was 63 (52–74) years, 155 (64.0%) were men, and 57 (23.6%) patients reached the primary end point. Baseline soluble ACE2 was elevated in COVID-19 but was not associated with disease severity or mortality. In contrast, an upward trajectory of soluble ACE2 at repeat sampling was independently associated with an elevated risk of mortality and incidence of acute myocardial injury and circulatory shock. Similarly, an increase in soluble tumor necrosis factor receptor levels was also associated with adverse outcomes. Plasma Ang I, Ang 1-7 (angiotensin 1–7) levels, and the Ang 1-7/Ang II (angiotensin II) ratio were elevated during SARS-CoV-2 infection related to downregulation of ACE activity at baseline. Moreover, patients having an upward trajectory of soluble ACE2 were characterized by an imbalance in the Ang 1-7/Ang II ratio. The observed dysregulation of ACE2 and angiotensin peptides with disease progression suggest a potential role of ADAM17 inhibition and enhancing the beneficial Ang 1-7/Mas axis to improve outcomes against SARS-CoV-2 infection.